Integrated system for improving the visibility trought the side windows of the motor vehicles - Coman, Isabele-Maria (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This study presents an innovated idea that includes the development and implementation of an integrated system to improve visibility through the side windows of the motor vehicles. In our days, one important thing is the security of passengers and drivers, especially when their job is closely related to driving a motor vehicle. Therefore, the visibility thought these windows, in particular in adverse rain or snow conditions, is very important to ensure the safety of the driver and passengers. To ensure the increased visibility, the system must be also sealed and easy to operate to comply with all current rules and regulations.